Analysis Of The Level Of Service User Satisfaction With Services At Gilimanuk Crossing Port During The Covid-19 Pandemic In 2021 - Chairul Insani Ilham; Elfita Agustini; Kadek Melinia Risma Dewi (IWJ : Inland Waterways Journal, 2021)
Gilimanuk Crossing Port is a crossing port that has a very important role for the community, especially on the island of Bali and Java as a moving bridge that connects the road network that is cut off due to the waters to transport passengers, goods, and vehicles. Based on the observations, there are several problems in existing conditions at Gilimanuk Crossing Port, namely waiting rooms and gangways that do not function properly, pedestrians who enter / disembark the ship still through trestle,lack of facilities for passengers with special needs, and lack of attention of officers to maintain health protocols of passengers at Gilimanuk Crossing Port. The methods used to analyze problems are Importance Performance Analysis and Customer Statisfaction Index based on aspects of Tangibility, Reliability, Responsiveness, Assurance, and Emphaty. The results of the analysis obtained a passenger satisfaction index of 61.5% and there are 5 (five) service attributes in quadrant I in the cartesius diagram importance performance analysis which is a priority to be improved and improved quality. The results of the analysis of the study include officers at Gilimanuk Crossing Port are less assertive with service users who violate health protocols such as not keeping their distance, not washing their hands and neglecting to use masks; There are still pedestrian passengers passing through the trestle so that there is a lack of security and safety of passengers and vehicles; Lack of hand washing facilities /handsanitizer; There are no facilities available for passengers with special needs to get on /off the ship.